VOLUME DE MADEIRA EM CLONES DE EUCALIPTO SUBMETIDOS A DESRAMA ARTIFICIAL. - Teixeira, Gabriel; Hayd, Norton; Vera, Damaris; Cacau, Filipe; Dos Santos, Ana Luiza; Arestides, Daniela (ANAIS DO ENIC, 2018)
-